[18F]AV‐1451 PET in behavioral variant frontotemporal dementia due to MAPT mutation. Issue 12 (18th October 2016) - Bevan Jones, W. Richard; Cope, Thomas E.; Passamonti, Luca; Fryer, Tim D.; Hong, Young T.; Aigbirhio, Franklin; Kril, Jillian J.; Forrest, Shelley L.; Allinson, Kieren; Coles, Jonathan P.; Simon Jones, P.; Spillantini, Maria G.; et al.
Abstract: The validation of tau radioligands could improve the diagnosis of frontotemporal lobar degeneration and the assessment of disease‐modifying therapies. Here, we demonstrate that binding of the tau radioligand [ 18 F]AV‐1451 was significantly abnormal in both magnitude and distribution in a patient with familial frontotemporal dementia due to a MAPT 10 + 16C>T gene mutation, recapitulating the pattern of neuropathology seen in her father. Given the genetic diagnosis and the non‐Alzheimer's pathology, these findings suggest that [ 18 F]AV‐1451 might be a useful biomarker in primary tauopathies. Largerscale in vivo and post‐mortem studies will be needed to assess the technique's specificity.